Signal transducer and activator of transcription‐3 (Stat3) plays a critical role in implantation via progesterone receptor in uterus. Issue 7 (26th March 2013) - Lee, Jae Hee; Kim, Tae Hoon; Oh, Seo Jin; Yoo, Jung‐Yoon; Akira, Shizuo; Ku, Bon Jeong; Lydon, John P.; Jeong, Jae‐Wook
Abstract : Recent studies have shown that activation of the signal transducer and activator of transcription‐3 ( Stat3 ) is required for decidualization, interacting with progesterone receptor (PR) in uterus. Based on previous reports, we hypothesized that crosstalk between STAT3 and PR signaling is required for successful implantation. To identify the interaction between STAT3 and PR isoforms, we performed immunoprecipitation following transient cotransfection and found that STAT3 physically interacted with PR‐A, which is known to be important for uterine development and function, but not with PR‐B. To further investigate the role of Stat3 in uterine function, Stat3 was conditionally ablated only in the PR‐positive cells ( PR cre/+ Stat3 f/f ; Stat3 d/d ). Our studies revealed that ovarian function and uterine development of Stat3 d/d mice were normal. However, Stat3 d/d female mice were infertile due to defective embryo implantation. Unlike Stat3 f/f mice, Stat3 d/d mice exhibited an unclosed uterine lumen. Furthermore, uteri of Stat3 d/d mice were unable to undergo a well‐characterized hormonally induced decidual reaction. The expression of stromal PR was decreased during decidualization and preimplantation period in Stat3 d/d mice, and PR target genes were significantly down‐regulated after progesterone induction. Our results suggest that STAT3 and PR crosstalk is required for successful implantation in the mouse uterus.—Lee, J. H., Kim, T. H., Oh, S. J., Yoo, J.‐Y., Akira, S., Ku, B. J., Lydon, J. P., Jeong, J.‐W. Signal transducer and activator of transcription‐3 ( Stat3 ) plays a critical role in implantation via progesterone receptor in uterus. FASEB J. 27, 2553–2563 (2013). www.fasebj.org